DASAR-DASAR PEMIKIRAN EKONOMI ISLAM - Subhan, Moh. (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2020)
Islamic economics as a new discipline and system, its presence is inseparable from the incompleteness of the existing economic system in solving economic problems which includes 3 basic aspects, namely what, haw and for whom. With a basic concept consisting of Tauhid, al-Adl, Nubuwah, Ma'ad, and Islamic economic khilafah, it appears that offers an integrative solution between world interests guided by normative theological values. Therefore, with 3 main characters which are basically derivative principles from the above basic concepts, namely social justice, freedom to act and multypel ownership of Islamic economics trying to align the above mission. With a descriptive approach to book analysis entitled Islamic Economic Principles is built. This article, which is a Book Review, tries to discuss Muhammad's work. There are 3 main ideas that are tried to be presented. The first one talks about the Islamic economic ontological framework which includes the configuration and principles of Islamic economics. The second one talks about contemporary economic problems framed in the value-free paradigm variables and issues surrounding liberalization. The three alternative offers for today's problems using the Islamic economic paradigm. Among the offers included the idea of ​​empowering the micro economy, which so far has been marginalized in the dominant economic system by capital forces.